Characteristic process variables during the Osmotic Dehydration of stone fruits: Experimental values and correlations between components content - Rodríguez, Anabel (2015)
Stone fruits (plums, peaches, nectarines, cherries and apricots) are widely consumed fresh or processed. Osmotic dehydration – immersion of food pieces in hypertonic solutions – is often used as a pretreatment to further conservation procedures for these fruits. Usually, it is characterized determining the variation with time of water loss and solution solids gain. Both variables depend on food size, shape, structure and process conditions, and there are no general correlations for their variation. As an alternative, it is important to develop relations between water and soluble solids content independent of product characteristics and process conditions. In this work, we developed experimental values of relevant variables for stone fruits dehydrated in glucose or sorbitol and included them in linear correlations between water content and soluble solids for different stone fruits dehydrated in sugar or polyalcohol solutions and in a general linear correlation that allows to characterize both properties with only one rapid determination (of any of both). Practical Applications Linear correlations for the variation of soluble solids content as a function of water content during osmotic dehydration were generalized to a unique linear regression equation independent of type of fruit and/or solute and valid for any process condition, which allows to characterize both properties with only one rapid determination (of any of both). This correlation can be easily used under process conditions to monitor the advance of osmotic dehydration of fruits.